Circulating CXCR5⁺CD4⁺ T Follicular-Like Helper Cell and Memory B Cell Responses to Human Papillomavirus Vaccines. - Ken Matsui; Joseph W Adelsberger; Troy J Kemp; Michael W Baseler; Julie E Ledgerwood; Ligia A Pinto (PLoS ONE)
Through the interaction of T follicular helper (Tfh) cells and B cells, efficacious vaccines can generate high-affinity, pathogen-neutralizing antibodies, and memory B cells. Using CXCR5, CXCR3, CCR6, CCR7, PD1, and ICOS as markers, Tfh-like cells can be identified in the circulation and be classified into three functionally distinct subsets that are PD1+ICOS+, PD1+ ICOS-, or PD1-ICOS-. We used these markers to identify different subsets of CXCR5+CD4+ Tfh-like cells in response to highly immunogenic and efficacious vaccines for human papillomaviruses (HPV): Cervarix and Gardasil. In this small study, we used PBMC samples from 11 Gardasil recipients, and 8 Cervarix recipients from the Vaccine Research Center 902 Study to examine the induction of circulating Tfh-like cells and IgD-CD38HiCD27+ memory B cells by flow cytometry. PD1+ICOS+ CXCR3+CCR6-CXCR5+CD4+ (Tfh1-like) cells were induced and peaked on Day (D) 7 post-first vaccination, but not as much on D7 post-third vaccination. We also observed a trend toward increase in PD1+ICOS+ CXCR3-CCR6-CXCR5+CD4+ (Tfh2-like) cells for both vaccines, and PD1+ICOS+ CXCR3-CCR6+CXCR5+CD4+ (Tfh17-like) subset was induced by Cervarix post-first vaccination. There were also minimal changes in the other cellular subsets. In addition, Cervarix recipients had more memory B cells post-first vaccination than did Gardasil recipients at D14 and D30. We found frequencies of memory B cells at D30 correlated with anti-HPV16 and 18 antibody titers from D30, and the induction levels of memory B cells at D30 and PD1+ICOS+Tfh1-like cells at D7 post-first vaccination correlated for Cervarix. Our study showed that induction of circulating CXCR5+CD4+ Tfh-like subsets can be detected following immunization with HPV vaccines, and potentially be useful as a marker of immunogenicity of vaccines. However, further investigations should be extended to different cohorts with larger sample size to better understand the functions of these T cells, as well as their relationship with B cells and antibodies.